Molecular Detection and Prevalence of, Cryptosporidium Parvum, Entamoeba Histolytica and Giardia Lamblia among Patients with Diarrhea at Al- Rifea city/Thi-Qar Province - Bassad Akrab Al- Aboody (Journal of Global Pharma Technology, 2018)
Diarrhea is defined as having extra stools than are usual for that individuals or as passage of watery stool for more than three times in 24 hours, caused by various pathogens such as bacteria, viruses and parasites and protozoa consider as important causes of diarrhea and other gastrointestinal infections in humans they include mostly Cryptosporidium parvum, Entamoeba histolytica and Giardia lambella, this study aimed to determined the prevalence of parasitic agents in stool samples of diarrheic patients , this study is carried out in Thi –Qar Province / Al-Refaie district in Al-Refaie general Hospital which included collection of stool samples from diarrheic patients at a period extended from October / 2017 – January / 2018 , (96) stool samples taken from patients with different ages to both sexes examined by PCR technique. The results showed The percentage of positive samples were 63.5% while 36.5% was negative C. parvum (11.9%), E. histolytica (22.6%) and G. lamblia (65.5%), no significant statistical differences between males, females and between Urban and Rural areas while there was significant statistical differences between age groups (the highest rate in less than 1 – 10 years and lowest age group was (11 – 20 years).Keywords: Cryptosporidium parvumm, Entamoeba histolytica and Gardia lamblia, Polymerase chain reaction (PCR), Protozoa.